Level of Anxiety and Depression in Post-Facial Trauma Patients - Rahim, Muhammad; Ghauri, Bushra; Khan, Muhammad Azad; Kanwal, Sana; Khan, Arbab Zarak; Razzaq, Syed Zeenat (Biological and Clinical Sciences Research Journal, 2025)
Maxillofacial trauma is a significant public health problem worldwide and is frequently associated with long-term physical, social, and psychological consequences. Patients sustaining facial injuries are particularly vulnerable to mental health disorders, including anxiety and depression, which may adversely affect recovery and quality of life. Objective: To determine the frequency and severity of anxiety and depression among patients presenting with post-facial trauma at a tertiary care hospital in Quetta, Pakistan. Methods: A descriptive cross-sectional study was conducted in the Department of Oral and Maxillofacial Surgery, Bolan University of Medical and Health Sciences (BUMHS), Quetta, over six months from 11 September 2021 to 10 March 2022. Adult patients with a history of facial trauma who met the inclusion criteria were enrolled using non-probability consecutive sampling. Anxiety and depression were assessed using the Hospital Anxiety and Depression Scale (HADS). Data were analyzed to determine the distribution of anxiety and depression severity. Results: The mean age of participants was 51.20 ± 12.48 years. Male patients constituted 71.4% of the sample, while females accounted for 28.6%. Based on HADS scoring, 10.5% of patients exhibited no symptoms of anxiety or depression, 35.2% demonstrated borderline symptoms, and 54.3% showed a definite level of anxiety and depression. Conclusion: Anxiety and depression are highly prevalent among patients with post-facial trauma. Routine psychological screening should be integrated into the management of facial trauma patients to enable early identification and timely intervention. Larger, multicenter studies are recommended to further explore psychosocial outcomes in this population.